TELAAH LITERATUR TERHADAP MODEL PEMBELAJARAN KETERAMPILAN BERBAHASA DI SEKOLAH DASAR PADA KURIKULUM MERDEKA - Liana Siburian; Margaretha Situmorang; Friskila Sihotang; Auguslina Sitinjak; Sesilia Ana Yunita Silaen (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT The implementation of the Merdeka Curriculum requires student-centered language learning; however, a comprehensive synthesis of the most relevant instructional models for elementary schools remains limited. This study aims to describe language learning models, identify their strengths, and analyze the challenges of their implementation within the Merdeka Curriculum. The study employed a descriptive qualitative approach using the library research method. Data were collected from articles indexed in Google Scholar, Garuda, and university journal portals. Based on predetermined inclusion criteria, 30 articles were selected and analyzed through data reduction, data display, and conclusion drawing. The novelty of this study lies in providing a comprehensive synthesis of the most relevant language learning models to support the implementation of the Merdeka Curriculum in elementary schools. The findings reveal a consistent pattern indicating that Problem-Based Learning, Project-Based Learning, Discovery Learning, Cooperative Learning, and differentiated instruction effectively enhance students' listening, speaking, reading, and writing skills through active, collaborative, and contextual learning. The main challenges include limited teacher competence, inadequate learning resources, and suboptimal implementation of differentiated instruction. The study concludes that the successful implementation of the Merdeka Curriculum depends on selecting adaptive, student-centered instructional models; therefore, strengthening teachers' professional competence and developing innovative instructional resources are essential strategic efforts. ABSTRAK Implementasi Kurikulum Merdeka menuntut pembelajaran keterampilan berbahasa yang berpusat pada peserta didik, namun belum tersedia sintesis komprehensif mengenai model pembelajaran yang paling relevan untuk diterapkan di sekolah dasar. Penelitian ini bertujuan mendeskripsikan model pembelajaran keterampilan berbahasa, mengidentifikasi keunggulannya, serta menganalisis tantangan implementasinya. Penelitian menggunakan pendekatan kualitatif deskriptif dengan metode library research. Data diperoleh melalui penelusuran artikel pada Google Scholar, Garuda, dan portal jurnal perguruan tinggi. Berdasarkan kriteria inklusi, diperoleh 30 artikel yang dianalisis melalui reduksi data, penyajian data, dan penarikan kesimpulan. Kebaruan penelitian ini terletak pada sintesis model pembelajaran keterampilan berbahasa yang paling relevan dalam implementasi Kurikulum Merdeka. Hasil penelitian menunjukkan pola temuan bahwa Problem Based Learning, Project Based Learning, Discovery Learning, Cooperative Learning, dan pembelajaran berdiferensiasi efektif meningkatkan keterampilan menyimak, berbicara, membaca, dan menulis melalui pembelajaran aktif, kolaboratif, dan kontekstual. Kendala utama meliputi keterbatasan kompetensi guru, sumber belajar, dan penerapan pembelajaran berdiferensiasi. Disimpulkan bahwa keberhasilan implementasi Kurikulum Merdeka bergantung pada pemilihan model pembelajaran yang adaptif dan berpusat pada peserta didik, sehingga penguatan kompetensi guru serta pengembangan perangkat pembelajaran inovatif menjadi langkah strategis.